Improvement of oil recovery factor in tight reservoirs: A laboratory approach based on carbon dioxide enhanced oil recovery methods - Zhang, Chuanbao; Wu, Gang; Huang, Hao; Zhan, Hongyang (Frontiers in Energy Research, 2022)
Production from unconventional oil reservoirs have always been a critical issue for the oil industry. In this regard, we implemented a set of experimental scenarios contained CO2/N2 cyclic injection, the foams generated by nitrogen and carbon dioxide, cyclic carbon dioxide injection, and combination effect of carbon dioxide and surfactant enhanced oil recovery methods. As water injection has reached a plateau around two pore volume injection, we continued the tests from two pore volume injection for different scenarios. Carbon dioxide is more feasible than nitrogen, it can mobilize more in the pore throats and provided higher oil recovery factor. Generated foam with CO2/N2 has increased oil recovery factor about 34.95% while it’s about 28% and 32.56% for generated foam by N2 and CO2. Moreover, according to the results of this study, the incremental oil recovery factor for surfactant flooding, carbonated water flooding and carbonated water with surfactant flooding are measured 4.9%, 8.5%, and 10.6% respectively.